Synthesis and Properties of 3-Hexadecyloxy-2-hydroxypropyl Triethyl Ammonium Chloride - Hao, Yulan; Wang, Jian; Yuan, Dandan; Qi, Ying; Zhang, Rongming (Asian Journal of Chemistry, 2014)
3-Hexadecyloxy-2-hydroxypropyl triethyl ammonium chloride was synthesized by using hexadecanol, triethylamine, epichlorohydrin, etc. as raw materials. The surface properties of product were studied e.g., critical micelle concentration, surface tension and so on. The product shows good surface activity. The corrosion inhibition performance of product to A3 carbon steel was studied in acidic medium. Given the conditions that in acidic medium, the immersion lasted for 72 h, under 25 °C and the concentration of product is 0.40 mmol/L, the corrosion inhibition rate is 93.61 % over A3 steel. The result showed that 3-hexadecyloxy-2-hydroxypropyl triethyl ammonium chloride has good capacity in inhibiting corrosion.